Safety and Efficacy of Mavacamten and Aficamten in Patients With Hypertrophic Cardiomyopathy - Bryton J. Davis; Hailey Volk; Olives Nguyen; Daniel Kamna; Hongya Chen; Roberto Barriales‐Villa; Pablo Garcia‐Pavia; Iacopo Olivotto; Anjali T. Owens; Caroline J. Coats; Theodore P. Abraham; Scott D. Solomon; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Cardiac myosin inhibitors were recently developed to address the underlying pathophysiology of hypertrophic cardiomyopathy and to improve symptoms and quality of life. In this review, we evaluated the pharmacologic profile and clinical outcomes for mavacamten and aficamten, 2 cardiac myosin inhibitors investigated in symptomatic hypertrophic cardiomyopathy. Methods and Results Using a systematic search, 10 clinical trials with safety and efficacy data for either drug in obstructive hypertrophic cardiomyopathy (oHCM) and nonobstructive hypertrophic cardiomyopathy were included. Additionally, we included data from regulatory agencies. Both drugs demonstrated substantial benefit in reducing left ventricular outflow tract obstruction (Valsalva left ventricular outflow tract gradients improved by −45 mm Hg or better), symptom burden (placebo‐corrected New York Heart Association class improvement ≥1 of at least 30%), and cardiac biomarkers (geometric mean ratio of 0.2 for N‐terminal pro‐B‐type natriuretic peptide) while improving exercise parameters (improved placebo‐corrected peak oxygen consumption of at least 1.4 to 1.8 mL/kg per minute) in patients with oHCM. Both drugs were generally well‐tolerated, although patients on mavacamten had higher rates of treatment interruption (partly protocol‐driven, 8.7% versus 0.5%, respectively, in oHCM) due to left ventricular ejection fraction reduction, atrial fibrillation (11.5 versus 4.1 per 100 patient‐years, respectively, in oHCM), and heart failure (1.7 versus 0.0 per 100 patient‐years, respectively, in oHCM) compared with aficamten. These comparisons are limited by a shorter exposure duration to aficamten, and longer follow‐up is needed. The data in nonobstructive hypertrophic cardiomyopathy are derived from phase II trials, with phase III trials ongoing. Conclusions Mavacamten and aficamten represent effective medications for the treatment of symptomatic oHCM.